(untitled) (American Journal of Islam and Society, 1997)
General psychology includes many areas of investigation: biological bases of behavior, sensation and perception, consciousness and attention, motivation and emotion, conditioning, learning, cognition, language, thinking, remembering and forgetting, intelligence, and personality. During the first half of the twentieth century, psychologists classified themselves as structuralists, functionalists, behaviorists, gestaltists, psychoanalysts, existentialists, humanists, or cognitivists. Today, such classifications are little used in the West. If one looks at the publications of the American Psychological Association and the British Psychological Society, psychologists classify themselves according to their fields or specific topic of hterest, such as social psychology, developmental psychology, abnormal psychology, psychotherapy, counseling, occupational psychology, psychometrics, media, women, and so on. Several tools are used in psychology to study behavior, among them surveys, questionnaires, interviews, observations, experiments, and tests. Psychology is defined as the scientific study of human behavior, and its theories and methods are considered scientific and universal. According to this understanding, there are four important terms that need ...